Evolution of the time and spatial photoresponse instabilities of the sensors based on CdZnTe crystals - But, A.V.; Mygal, V.P.; Phomin, A.S. (Functional Materials, 2009)
By comparing the I(t)-dl/dt diagrams, wavelet-spectrograms of kinetics I(t) and coordinate dependences I(y) of photocurrent, the features of time and spatial photoresponses of CdZnTe crystals are revealed and studied. It is shown that switching of the sensor from the steady state to unsteady one is accompanied by the photoresponse signal energy redistribution from high to low frequencies and a gradual transition of the instability process to the larger scale levels. Шляхом співставлення діаграм I(t)-dl/dt, вейвлет-спектрограм кінетики I(t) та залежностей І(у) виявлено та досліджено особливості часового і просторового фотовідкликів кристалів CdZn Те. Показано, що перемикання сенсора зі стійкого стану у нестійкий супроводжується перерозподілом енергії сигналу фотовідклику з високих частот на низькі та поступовим переходом процесу нестійкості на більш великі масштабні рівні. Путем сопоставления диаграмм I(t)-dl/dt, вейвлет-спектрограмм кинетики I(t) и зависимостей фототока от координаты I(y) выявлены и исследованы особенности временного и пространственного фотооткликов кристаллов CdZnТе. Показано, что переключение сенсора из устойчивого состояния в неустойчивое сопровождается перераспределением энергии сигнала фотоотклика с высоких частот на низкие и постепенным переходом процесса неустойчивости на более крупные масштабные уровни.